Noninvasive follow-up strategy after pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension. Issue 2 (16th May 2022) - Ruigrok, Dieuwertje; Handoko, M. Louis; Meijboom, Lilian J.; Nossent, Esther J.; Boonstra, Anco; Braams, Natalia J.; van Wezenbeek, Jessie; Tepaske, Robert; Tuinman, Pieter Roel; Heunks, Leo M.A.; Vonk Noordegraaf, Anton; de Man, Frances S.; et al.
Background: The success of pulmonary endarterectomy (PEA) for chronic thromboembolic pulmonary hypertension (CTEPH) is usually evaluated by performing a right heart catheterisation (RHC). Here, we investigate whether residual pulmonary hypertension (PH) can be sufficiently excluded without the need for a RHC, by making use of early post-operative haemodynamics, or N-terminal pro-brain natriuretic peptide (NT-proBNP), cardiopulmonary exercise testing (CPET) and transthoracic echocardiography (TTE) 6 months after PEA. Methods: In an observational analysis, residual PH after PEA measured by RHC was related to haemodynamic data from the post-operative intensive care unit time and data from a 6-month follow-up assessment including NT-proBNP, TTE and CPET. After dichotomisation and univariate analysis, sensitivity, specificity, positive predictive value, negative predictive value (NPV) and likelihood ratios were calculated. Results: Thirty-six out of 92 included patients had residual PH 6 months after PEA (39%). Correlation between early post-operative and 6-month follow-up mean pulmonary artery pressure was moderate (Spearman rho 0.465, p<0.001). Early haemodynamics did not predict late success. NT-proBNP >300 ng·L −1 had insufficient NPV (0.71) to exclude residual PH. Probability for PH on TTE had a moderate NPV (0.74) for residual PH. Peak oxygen consumption ( V ′O2 ) <80% predicted had the highest sensitivity (0.85) and NPV (0.84) for residual PH. Conclusions: CPET 6 months after PEA, and to a lesser extent TTE, can be used to exclude residual CTEPH, thereby safely reducing the number of patients needing to undergo re-RHC after PEA. In approximately one-third to one-half of CTEPH patients, residual pulmonary hypertension after pulmonary endarterectomy can be excluded based on cardiopulmonary exercise testing or echocardiography, without the need for right heart catheterisation https://bit.ly/3pbj2Ge